The Breast Response to Estrogenic Stimulation in Transwomen Classification: Evaluation of Breast Response to Estrogenic Stimulation in Transwomen. Issue 4 (October 2021) - Alcon, Andre; Wang, Eric; Oliver-Allen, Hunter; Srinivasa, Dhivya; Kim, Esther A.
Abstract : Background: Hormone therapy with exogenous estrogen and/or spironolactone is commonly used in transfemales to induce breast development. However, inherent differences in adult male and female anatomy create persistent deformities and inadequate gender congruency despite glandular breast development. This includes nipple characteristics, position of inframammary fold, and the distribution of breast tissue. Accordingly, the Tanner stages do not accurately reflect these persistent deformities because they relate to breast development in transwomen. Herein, we describe a classification system for breast development in transwomen treated with hormone therapy. Methods: Ninety-nine transfemale patients who underwent breast augmentation from 2014 to 2018 were retrospectively reviewed and categorized using a novel scheme, the Breast Response to Estrogenic Stimulation in Transwomen (BREST) scale. Preoperative demographics, anatomic measurements, surgical technique, and postoperative results were also compared among BREST types. Results: Most patients were rated as BREST type II (25%) or type IV (37%). The BREST scale exhibited moderate interrater reliability ( κ = 0.58) between 3 plastic surgeons. Objective breast measurements such as sternal notch-to-nipple distance and nipple-to-inframammary fold distance correlated with the BREST scale. Multivariate logistical regression identified the nipple-to-inframammary fold distance and different between the bust and chest circumference as the strongest predictors of BREST type (odds ratio, 2.57 and 1.96, respectively). Body mass index was not a predictor of BREST type after controlling for confound variables on multivariate analysis. Conclusions: The BREST scale uniquely captures the differences in breast phenotypes in transgender women according to hormone therapy response. Although some subjectivity exists with moderate interrater reliability, the BREST scale correlates with objective breast measurements. The BREST scale provides a transwoman-specific metric allowing for a common language in assessment of transgender breast development and optimal communication among providers, different specialties, and insurance companies.